(untitled) (Texas Journal of Philology, Culture and History, 2025)
The article examines the formation and development of ecolinguistics, its theoretical and methodological foundations, and its role in interdisciplinary integration. It highlights the concept of language ecology proposed by Einar Haugen and its further development by subsequent researchers. The scientific significance of studying language in ecological, social, and cultural contexts, as well as the role of the new ecological thinking concept in linguistics, is explained.